2000
DOI: 10.1016/s0735-1097(00)00697-5
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein cholesterol and coronary microvascular dysfunction in hypercholesterolemia

Abstract: Low density lipoprotein cholesterol but not TC correlated inversely with CFR in hypercholesterolemic subjects. Thus, LDL-induced coronary microvascular dysfunction could play an important role in the pathogenesis of coronary artery disease and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(110 citation statements)
references
References 64 publications
6
97
2
5
Order By: Relevance
“…The great interest for this issue, originated from previous clinical evidence that endothelial-dependent vasodilation as well as pharmacological (adenosine mediated) and metabolic coronary reserve of atherosclerotic-free or non flow-limiting atherosclerotic vessels at angiography, was reduced in hypercholesterolemic patients [12] [13] and could be normalized with the use of cholesterol-lowering strategies or NO donors [14]- [19]. Although a different contribution of total, LDL and HDL cholesterol to the impairment of coronary reserve was evidenced from previous experimental studies, they demonstrated an inhibitory effect of oxidized LDL and a protective role of HDL only on endothelium-dependent arterial vasodilation [20], concordant with clinical observations [21] [22]. On the other hand, the interplay between LDL and HDL and the association with other circulatory factors (cytokines, cell adhesion molecules) in coronary microvascular dysfunction are still partly unexplored.…”
Section: Introductionsupporting
confidence: 75%
“…The great interest for this issue, originated from previous clinical evidence that endothelial-dependent vasodilation as well as pharmacological (adenosine mediated) and metabolic coronary reserve of atherosclerotic-free or non flow-limiting atherosclerotic vessels at angiography, was reduced in hypercholesterolemic patients [12] [13] and could be normalized with the use of cholesterol-lowering strategies or NO donors [14]- [19]. Although a different contribution of total, LDL and HDL cholesterol to the impairment of coronary reserve was evidenced from previous experimental studies, they demonstrated an inhibitory effect of oxidized LDL and a protective role of HDL only on endothelium-dependent arterial vasodilation [20], concordant with clinical observations [21] [22]. On the other hand, the interplay between LDL and HDL and the association with other circulatory factors (cytokines, cell adhesion molecules) in coronary microvascular dysfunction are still partly unexplored.…”
Section: Introductionsupporting
confidence: 75%
“…In diabetes, endothelial dysfunction is considered as a critical and initiating factor in the development of chronic diabetic macro-and microvascular disease and it becomes a great challenge to understand its mechanisms and aetiology [43]. Most of the studies had focused on hyperglycaemia as the main cause of this impaired vascular function but compelling evidence in healthy [44], hypercholesterolaemic [45,46] and diabetic patients [47] suggests that LDL cholesterol concentration could also be a major cause of alteration of the endothelial function. However, in diabetic patients, impairment of endothelial function occurs even under normocholesterolaemic conditions with a normal LDL concentration [48] and intensive lipid lowering therapy by statins failed to improve vascular reactivity in several studies [49].…”
Section: Discussionmentioning
confidence: 99%
“…Through the years, several reports using PET have demonstrated microvascular dysfunction in narrowly selected subsets of patients with specific cardiovascular risk factors such as smoking [23], dyslipidemia [24], hypertension [25], diabetes mellitus [26] and rheumatic diseases [27].…”
Section: Microvascular Disease and Treatment Monitoringmentioning
confidence: 99%